The pathogenesis of pulmonary hypertension – an update (Swiss Medical Weekly, 2015)
Elevation of the mean pulmonary arterial pressure to ≥25 mm Hg within the low-pressure system of the pulmonary circulation is defined as pulmonary hypertension. Pulmonary hypertension may be the consequence of various clinical and pathophysiological entities. Many of these conditions, however, result in a final common pathway of pathogenesis. This pathway is characterised by the triad of excessive vasoconstriction, microthrombosis and remodelling of pulmonary arteries. Remodelling is arguably the most important factor: its complex pathogenesis is not completely understood and no specific treatment directly targets vascular remodelling. This article aims to review the current understanding of the pathogenesis of pulmonary hypertension and to give insights in future developments in this evolving field.